(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2018)
This research focuses on the relationships between teacher knowledge and the teaching content with which Biology teachers deal in their daily teaching practices. This research seeks to understand the ways teachers use this knowledge to facilitate students’ learning of Biology. The methodological guidelines of the present study have been inspired on experiences of ethnographic studies to combine different procedures of data collection: questionnaires; interviews and classroom observations with field notes and video recording. The empirical design involved three public secondary schools, placed in the urban area of Vitória da Conquista, Bahia with the participation of six Biology teachers. In this work, throughout a triangulation process, the data produced with three of those six teachers were analyzed by means of a thematic content analysis, which allowed the identification of words, sentences or summaries, and a range of relationships present in the data. The results indicate that, in the production of school knowledge, teacher knowledge is translated into practice by a combination of different “ways of doing”, favoring students’ learning of biological contents. In this sense, these “ways of doing” indicate links between teacher knowledge and the biological content. The results also indicate that such links are results of teaching established routines within the school culture. The research argues that “ways of doing” are the outcomes of a more specific teacher’s experiential knowledge, that when articulated to other types of knowledge, shape the production of school knowledge.